Salivary DNA methylation panel to diagnose HPV-positive and HPV-negative head and neck cancers. Issue 1 (December 2016) - Lim, Yenkai; Wan, Yunxia; Vagenas, Dimitrios; Ovchinnikov, Dmitry; Perry, Chris; Davis, Melissa; Punyadeera, Chamindie
Abstract Background Head and neck squamous cell carcinoma (HNSCC) is a heterogeneous group of tumours with a typical 5 year survival rate of <40 %. DNA methylation in tumour-suppressor genes often occurs at an early stage of tumorigenesis, hence DNA methylation can be used as an early tumour biomarker. Saliva is an ideal diagnostic medium to detect early HNSCC tumour activities due to its proximity to tumour site, non-invasiveness and ease of sampling. We test the hypothesis that the surveillance of DNA methylation in five tumour-suppressor genes (RASSF1α, p16 INK4a, TIMP3, PCQAP /MED15 ) will allow us to diagnose HNSCC patients from a normal healthy control group as well as to discriminate between Human Papillomavirus (HPV)-positive and HPV-negative patients. Methods Methylation-specific PCR (MSP) was used to determine the methylation levels ofRASSF1α, p16 INK4a, TIMP3 andPCQAP /MED15 in DNA isolated from saliva. Statistical analysis was carried out using non-parametric Mann-Whitney'sU -test for individually methylated genes. A logistic regression analysis was carried out to determine the assay sensitivity when combing the five genes. Further, a five-fold cross-validation with a bootstrap procedure was carried out to determine how well the panel will perform in a real clinical scenario. Results Salivary DNA methylation levels were not affected by age. Salivary DNA methylation levels forRASSF1α, p16 INK4a, TIMP3 andPCQAP /MED15 were higher in HPV-negative HNSCC patients (n  = 88) compared with a normal healthy control group (n  = 122) (sensitivity of 71 % and specificity of 80 %). Conversely, DNA methylation levels for these genes were lower in HPV-positive HNSCC patients (n  = 45) compared with a normal healthy control group (sensitivity of 80 % and specificity of 74 %), consistent with the proposed aetiology of HPV-positive HNSCCs. Conclusions Salivary DNA tumour-suppressor methylation gene panel has the potential to detect early-stage tumours in HPV-negative HNSCC patients. HPV infection was found to deregulate the methylation levels in HPV-positive HNSCC patients. Large-scale double-blinded clinical trials are crucial before this panel can potentially be integrated into a clinical setting.